2023
DOI: 10.1101/2023.01.09.23284343
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnitude of work-related musculoskeletal disorders and ergonomic risk practices among medical laboratory professionals in Northwest Ethiopia: A cross-sectional study

Abstract: Objective: This study aimed to assess the magnitude of work-related musculoskeletal disorders (WMSDs) and ergonomic risk practices among medical laboratory professionals in North West Ethiopia. Design: Facility-based cross-sectional study Methods: Cross-sectional study design was employed among medical laboratory professionals (MLPs). The Nordic musculoskeletal questionnaire was adopted and used. In addition to questionnaires about socio-demographic characteristics and ergonomic risk practice, one-to-one inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A systematic review stated that in many African countries, the prevalence of any musculoskeletal disease ranged from 15 to 93.6% (12). Studies carried out on the working population of Ethiopia have also shown similar trend with prevalence varying between 47.7 and 81.5% (13)(14)(15)(16)(17). As various evidence studies indicated, these figures are likely attributed from the multiple effects of biomechanical, work organizational, psychosocial, and/or other individual factors (6,7,18,19).…”
Section: Introductionmentioning
confidence: 97%
“…A systematic review stated that in many African countries, the prevalence of any musculoskeletal disease ranged from 15 to 93.6% (12). Studies carried out on the working population of Ethiopia have also shown similar trend with prevalence varying between 47.7 and 81.5% (13)(14)(15)(16)(17). As various evidence studies indicated, these figures are likely attributed from the multiple effects of biomechanical, work organizational, psychosocial, and/or other individual factors (6,7,18,19).…”
Section: Introductionmentioning
confidence: 97%